Efektivitas Media Dakon terhadap Motivasi Belajar Matematika Siswa Kelas V SD Negeri Ngabeyan 3 Kartasura Tahun Pelajaran 2016/2017 - Handayani, Nurul Ary, Honest Ummi Kaltsum, S.S., M.Hum (2017)
The purpose of this research is to know: (1) influence of factor tree media to motivation to learn mathematics of grade V student of SD Negeri Ngabeyan 3 Kartasura. (2) the influence of dakon media on the motivation to learn mathematics of grade V students of SD Negeri Ngabeyan 3 Kartasura. (3) the effectiveness of dakon media versus factor tree on the motivation of students in grade V SD Negeri Ngabeyan 3 Kartasura. This research is a quantitative research with experimental design. The population in this research is the students of grade V SD Negeri Ngabeyan 3 Kartasura academic year 2016/2017. The sampling technique used in this study is saturated sampling that is all the population used as a sample. Data collection techniques in this study using questionnaires, observation and documentation. The results of this study indicate that (1) Media factor tree affect the motivation to learn mathematics of grade V students of SD Negeri Ngabeyan 3 Kartasura. (2) Dakon media have an effect on the motivation to learn mathematics of grade V students of SD Negeri Ngabeyan 3 Kartasura. 3) Media dakon more effective than factor tree in improving motivation of studying student mathematics class V in SD Negeri Ngabeyan 3 Kartasura year lesson 2016/2017. This is indicated by t = -10,055 with significance value (p) of 0.000 and mean learning motivation using dakon media is higher than mean of learning motivation using factor tree (80,05> 62, 25).